Breach Rate Analysis of Pedicle Screw Instrumentation using Free-Hand Technique in the Surgical Correction of Adolescent Idiopathic Scoliosis - Librianto, Didik (J Orthop Case Rep, 2021)
INTRODUCTION: Free-hand technique is one of the techniques used by spine surgeon during pedicle screw instrumentation of surgical correction of spinal deformities, including scoliosis. The previous studies showed that this technique is safe. However, some inherent factors may influence its outcomes, including screw breaching which is potentially violates spinal cord and other intimate structures. To confirm the safety and accuracy of this technique, additional study measuring the breach rate of pedicle screw placement in scoliosis is mandatory. MATERIALS AND METHODS: We performed a retrospective study of patients with adolescent idiopathic scoliosis (AIS) from Fatmawati General Hospital, Jakarta, treated for surgical correction during a period of 2017–2018 using free-hand technique for pedicle screw instrumentation. Post-operative computed tomography scan (CT scan) was analyzed to measure the medial and lateral breaches. P < 0.05 was deemed to be statistically significant. RESULTS: A total of 94 pedicle screws from six female patients with AIS were included in our study. Overall breach occurred in 33% instrumented screws, the majority of it was a low-grade breach. Of the breached screws, medial and lateral breach occurred in 20% and 12% of screws, respectively. There were no differences in the overall, medial, and lateral breaches between thoracic and lumbar vertebrae (P > 0.05). Medial breach was significantly higher in middle thoracic segment compared to other thoracic segments (P = 0.048). Risk of medial breach was 3 times higher in the convex side of deformity (P = 0.012), whereas risk of lateral breach was 4.6 times higher in the concave side of the deformity (P = 0.021). CONCLUSION: The majority of breached screws were low-grade violation within the safe zone, with no neurological sequelae. Our study found that free-hand technique is safe and effective method of pedicle screw instrumentation for correction of AIS. Some inherent factors may influence the risk of pedicle screw breach.